The therapeutic potential of Melissa officinalis L. hydroalcoholic extract and rosmarinic acid in a rat asthmatic model: A study on anti-inflammatory and antioxidant effects - Vahideh Abbasnia; Mohammad Reza Khazdair; Delaram Eslimi Esfahani; Shahrbanoo Oryan; Mohsen Foadoddini (Mashhad University of Medical Sciences, 2024)
Objective: The article studies how Melissa officinalis L. extract and rosmarinic acid (RA) affect lung inflammation, pathology, and oxidative stress in rats with ovalbumin-induced asthma.Materials and Methods: Asthma was induced in rats using ovalbumin injection and inhalation. The study assessed lung inflammation, pathological changes, and oxidative stress in control, untreated asthmatic rats and three treatment groups. These groups received M. officinalis extract (50, 100, 200 mg/kg), RA (0.5, 1, 2 mg/kg), or dexamethasone (Dex) 1 mg/kg.Results: In the sensitized group, white blood cell counts, malondialdehyde, and nitrite levels increased significantly, while thiol levels and the activity of superoxide dismutase and catalase decreased (p<0.001). However, all treatment groups with the extract, RA, and Dex showed a significant reduction in total white blood cells, eosinophils, monocytes, malondialdehyde, and nitrite levels compared to the asthma group (p<0.001 in all groups). Thiol levels and catalase and superoxide dismutase activity were significantly higher in all treated groups with RA and high extract doses (p<0.001). Lung pathological changes were also significantly less severe in the treated groups with dexamethasone, plant extract, and RA compared to the asthma group (p<0.05 to p<0.001).Conclusion: This study showed that M. officinalis and RA have antioxidant and anti-inflammatory effects in an animal asthma model, suggesting their potential for treating asthma symptoms.